A Novel Approach To Information Spreading Models for Social Networks - Sayın, Burcu; Şahin, Serap; Şahin, Serap; Sayın, Burcu (International Academy, Research, and Industry Association (IARIA), 2017)
Analyzing and modelling the spreading of any information through a social network (SN) is an important issue in social network analysis. Proposed solutions for this issue do not only help observing the information diffusion but also serve as a valuable resource for predicting the characteristics of the network, developing network-specific advertising etc. Up-to-date approaches include probabilistic analysis of information spreading and the information cascade models. In this paper, we propose a hybrid model which considers an information spreading model, combines it with cascades and social behavior analysis. We propose a new hybrid usage approach to represent a real-world modelling for information spreading process.
The Sixth International Conference on Data Analytics, November 12 - 16, 2017, Barcelona, Spain
Keywords: Social network analysis; Information spreading; Information cascades